Pathogenic and genetic variability in Alternaria brassicae infecting rapeseed-mustard and evaluation of resistance sources - PREM NATH SHARMA, VEDNA KUMARI and ASHOK KUMAR*, ARUN KUMAR, ABHISHEK KATOCH (Indian Phytopathology, 2014)
Rapeseed-mustard is an important oilseed crop grown worldwide with Alternaria blight being one of the most devastating fungal diseases hampering production. Seven pathotypes (Abr1 to Abr7) of Alternaria brassicae were associated with disease losses in Himachal Pradesh while characterizing 32 isolates on differential set comprised of six Brassica species. Pathotype Abr4 being the most predominant and had compatible interaction with all six differential hosts. DNA fingerprinting using ISSR primers revealed wide genetic diversity among 32 isolates of A. brassicae grouped into five major clusters independent of pathotypes. Out of forty genotypes of rapeseed-mustard screened, no single genotypes resistant to all the pathotypes of pathogen was found. Genotype GS-05-1 of Brassica napus was found to be resistant against two pathotypes viz., Abr1 and Abr5 whereas, three genotypes viz., RH-8544, Pusa Swarnim and HC-9605 showed moderately resistant reaction to at least three pathotypes.